2023
DOI: 10.1111/1541-4337.13128
|View full text |Cite
|
Sign up to set email alerts
|

Application of chitosan nanoparticles in quality and preservation of postharvest fruits and vegetables: A review

Abstract: Chitosan is an interesting alternative material for packaging development due to its biodegradability. However, its poor mechanical properties and low permeability limit its actual applications. Chitosan nanoparticles (CHNPs) have emerged as a suitable solution to overcome these intrinsic limitations. In this review, all studies regarding the use of CHNPs to extend the shelf life and improve the quality of postharvest products are covered. The characteristics of CHNPs and their combinations with essential oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 184 publications
0
2
0
Order By: Relevance
“…However, with all nanoparticles, there is uncertainty about safety, particularly for food applications. While this applies to both inorganic and metal nanoparticles, heavy metal nanoparticles such as titanium or copper are concerns for food consumers’ health . Therefore, further research into compatibility of films with food packaging applications with a view toward food safety should be conducted.…”
Section: Modifications To Improve the Physicochemical Properties Of S...mentioning
confidence: 99%
“…However, with all nanoparticles, there is uncertainty about safety, particularly for food applications. While this applies to both inorganic and metal nanoparticles, heavy metal nanoparticles such as titanium or copper are concerns for food consumers’ health . Therefore, further research into compatibility of films with food packaging applications with a view toward food safety should be conducted.…”
Section: Modifications To Improve the Physicochemical Properties Of S...mentioning
confidence: 99%
“…Chitosan is a product formed after deacetylation of chitin with film-forming property (Assaf et al 2020). Studies have shown that chitosan, when coated on postharvest fruits, can not only effectively block the invasion of pathogenic fungi through mechanical barrier, but also induce fruit resistance by its hydrolysates (Wang et al 2023). On this basis, this study mainly discusses the inhibitory effect of chitosan on pathogenic fungi and its influence on antagonistic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-farming refers to the application of nanomaterials (NMs) or nanoparticles (NPs) in agricultural production [34]. This can be performed in different ways, including nano-priming of seeds to increase germination through the regulation of ROS [35], nanofertilization to increase crop productivity during the growing season [36], nano-pesticide application for plant protection [37], nano-sensors to support smart farming [38,39], nanoharvest [40] or nano-postharvest [41,42] applications to reduce food spoilage, and plant nano-bionics to enhance or modify plant functions [43]. Nanomaterials have the potential to enhance the productivity of crops by improving the delivery of nutrients, managing pest control, and supporting crop stress resilience [44].…”
Section: Introductionmentioning
confidence: 99%